Mesoporous Ni–Fe Alloys - Yu Okuno; Yoshiyuki Hattori; Tomonori Ohba; Katsumi Kaneko; Hirofumi Kanoh (Adsorption Science & Technology)
A nano-structured alloy of Ni and Fe was prepared using poly(vinyl alcohol) (PVA) as a polymer precursor, followed by the reduction of Ni 2+ and Fe 3+ ions to the corresponding metals by heat treatment of the PVA film containing the metal ions under an inert atmosphere. The alloy obtained was characterized by nitrogen adsorption studies, X-ray diffraction and electron microscopy measurements, and by X-ray photoelectron spectroscopy. The nano-structured alloy had the same crystal structure as that of metallic Ni although metallic Fe formed a different structure. The introduction of Fe atoms caused disorder and less crystallinity in the crystal structure of the alloy, whereas Ni atoms tended to maintain the original crystal structure. Nitrogen adsorption measurements at 77 K showed that the nano-structured Ni–Fe alloy contained mesopores of 4–10 nm in diameter.